Maternal Music Exposure during Pregnancy Influences Neonatal Behaviour: An Open-Label Randomized Controlled Trial - Ravindra Arya; Maya Chansoria; Ramesh Konanki; Dileep K. Tiwari (Hindawi Limited, 2012)
Objective. This study evaluated the effect of antenatal music exposure to primigravida healthy mothers on the behaviour of their term appropriate-for-date newborns assessed using Brazelton Neonatal Behavioral Assessment Scale (BNBAS). Methods. This was a single-centre, randomized, open-label controlled trial. Primigravida mothers aged 19-29 years, free of chronic medical diseases or significant deafness, with singleton pregnancy, with a gestation of 20 weeks or less, were randomized to listen to a pre-recorded music cassette for approximately 1 hour/day in addition to standard antenatal care (intervention arm) or standard care only (control arm). Perinatal factors with adverse effect on neonatal behaviour were deemed as protocol violations. Outcome measure included scores on 7 clusters of BNBAS. Primary analysis was per protocol. The trial is registered with ClinicalTrials.gov (NCT01278329). Results. One hundred and twenty-six newborns in the music group and 134 in the control group were subjected to BNBAS assessment. The infants of mothers exposed to music during pregnancy performed significantly better on 5 of the 7 BNBAS clusters. The maximal beneficial effect was seen with respect to orientation (ES 1.13, 95% CI 0.82-1.44, 𝑃<0.0001) and habituation (ES 1.05, 95% CI 0.53-1.57, 𝑃=0.0001). Conclusion. Prenatal music exposure to mother significantly and favourably influences neonatal behaviour.